2015
DOI: 10.1160/th14-11-0952
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII-A dynamics in acute myocardial infarction: a novel prognostic biomarker?

Abstract: After acute myocardial infarction (MI) the damaged heart has to be repaired. Factor XIII (FXIII) is considered a key molecule in promoting heart healing. FXIII deficiency was associated to cardiac rupture and anomalous remodelling in MI. During MI, FXIII contributes firstly to the intracoronary thrombus formation and shortly after to heal the myocardial lesion. To quantify the real contribution of FXIII in this process, and to explore its possible prognostic role, we monitored the FXIII-A subunit levels in 350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…The past few decades of research have shown FXIII to have multiple pleiotropic functions 12 . It is known to play roles in maintaining vascular permeability, in development of extracellular matrix in bone and cartilage, in fostering cardioprotective effects, as a first line of defense against invading pathogens and, as recently reported, in pre-adipocyte differentiation and arthritis 13 14 15 16 17 18 . Identification and cloning of the F13A1 and F13B genes, along with the recombinant expression of the FXIIIA 2 and B 2 subunits 19 20 21 , was followed by high-resolution structural determination of the FXIIIA 2 dimer in zymogenic forms 22 23 24 25 .…”
mentioning
confidence: 92%
“…The past few decades of research have shown FXIII to have multiple pleiotropic functions 12 . It is known to play roles in maintaining vascular permeability, in development of extracellular matrix in bone and cartilage, in fostering cardioprotective effects, as a first line of defense against invading pathogens and, as recently reported, in pre-adipocyte differentiation and arthritis 13 14 15 16 17 18 . Identification and cloning of the F13A1 and F13B genes, along with the recombinant expression of the FXIIIA 2 and B 2 subunits 19 20 21 , was followed by high-resolution structural determination of the FXIIIA 2 dimer in zymogenic forms 22 23 24 25 .…”
mentioning
confidence: 92%
“…Finally, it is clear that many biologic functions of FXIII have not been thoroughly elucidated. In addition to coagulation, FXIII may have roles in arthritis(50), adipogenesis(51), and cardiac repair(52, 53). It will be important to understand the impact of FXIII inhibition on these situations before the benefit of a FXIIIa antagonist can be realized in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the proangiogenic function of factor XIII is directed by the interaction of vascular endothelial growth factor receptor 2 and integrin aVb 3 on the cell membrane [51]. Certain studies showed that low factor XIIIA level correlated with a poor prognosis with regard to MI [52,53]. Therefore, MI could be differently affected by this function of factor XIII compared to CAD without MI.…”
Section: Discussionmentioning
confidence: 99%